Jackson Pollock, 1912-1956 : at the limit of painting - Emmerling, Leonhard, 1961-; Pollock, Jackson, 1912-1956. (Los Angeles : Taschen, 2009)
An introduction to the life and work of twentieth-century American artist Jackson Pollock, discussing his cultural and historical importance, and including a chronology and over one hundred color illustrations with explanatory captions.
Cover title: Pollock.
Originally published in 2003.
Includes bibliographical references (p. 96).
Adult
Keywords: Pollock, Jackson, -- 1912-1956 -- Criticism and interpretation; Pollock, Jackson, -- 1912-1956 -- Criticism; Abstract expressionism -- United States; Expressionism (Art) -- United States